2020
DOI: 10.1016/j.ijid.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Post-vaccine rotavirus genotype distribution in Nairobi County, Kenya

Abstract: Highlights This article reports post-vaccine rotavirus G and P genotypes in Nairobi County. G1P[8] dominance has decreased following the introduction of Rotarix. There has been an increased prevalence of G2 genotypes following Rotarix introduction. There has been a change in genetic diversity of rotavirus strains in Nairobi, Kenya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…In the post-vaccine introduction period, G3P [4] was the most frequent combination detected in MSD and LSD in 2016 and 2017, while G3P [8] was seen in LSD in 2018 and G9P [8] in MSD, LSD and controls in 2019. Our findings are in concordance with reports of African countries such as Botswana and Kenya in which G3P [4] was found after rotavirus vaccine introduction [42,43]. However, some studies reported G3P [8] in high frequency in cases of MSD in the post-vaccine introduction period in Mozambique [18] and other African countries such as Kenya reported G3P [8] and G9P [8] [44].…”
Section: Discussionsupporting
confidence: 91%
“…In the post-vaccine introduction period, G3P [4] was the most frequent combination detected in MSD and LSD in 2016 and 2017, while G3P [8] was seen in LSD in 2018 and G9P [8] in MSD, LSD and controls in 2019. Our findings are in concordance with reports of African countries such as Botswana and Kenya in which G3P [4] was found after rotavirus vaccine introduction [42,43]. However, some studies reported G3P [8] in high frequency in cases of MSD in the post-vaccine introduction period in Mozambique [18] and other African countries such as Kenya reported G3P [8] and G9P [8] [44].…”
Section: Discussionsupporting
confidence: 91%
“…The introduction of RV vaccination has succeeded in nearly halving the number of global RV deaths from 453,000 in 2008 to 215,000 in 2013 (Moyo et al, 2014; Tate et al, 2012). Indeed, RV vaccines continue to be successful in minimizing disease severity as well as hospitalizations and thus reducing mortality from RV infection, but the infection nevertheless remains ineradicable, showing multiple outbreaks and greater diversity of circulating RV genotypes in the post-vaccination period documented in our previous studies (Hoque et al, 2020 ; Okitsu et al, 2022 ) as well as by other groups (Gibory et al, 2022 ; Gikonyo et al, 2020 ; Tsugawa et al, 2021 ). A similar diversity of RV genotypes was observed in the present study at SW (Table 1 ).…”
Section: Discussionmentioning
confidence: 61%
“…Being a developed and industrialized nation, Japan still struggles against AGE-associated morbidity and economic losses throughout the year (Kawata et al, 2020 ). To prevent severe RV infections, Japan has introduced RV vaccines as voluntary vaccines since 2011 and included these in the national immunization program from October 2020, yet the diversity in RV genotypes and increasing trends of other diarrheal viruses have been found in post-RV-vaccination era worldwide including Japan (Gikonyo et al, 2020 ; Hoque et al, 2022a , 2022b , 2022c ; Tsugawa et al, 2021 ). However, after the emergence of the pandemic coronavirus disease-2019 (COVID-19) , the implementation of non-pharmaceutical interventions (NPIs) like social distancing, mask-wearing, increased hand hygiene, school closures, and working from home have proven effective to reduce COVID-19 along with many other infectious diseases including AGE (Eigner et al, 2021 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Globally G1, G2, G3, G4, G9, G12 genotypes in combination with P [4], P[6] and P[8] are predominant (Crawford et al, 2017). With the introduction of vaccines, there have been reports of increased circulation of one or more genotypes and occasional emergence of vaccine-derived strains (Dulgheroff et al, 2012;Gikonyo et al, 2020;Roczo-Farkas et al, 2018;Tanaka et al, 2017;Thanh et al, 2018;Zeller et al, 2010). In the 11-year national GARV surveillance network study (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016), G1P[8] was found to be the predominant genotype in all regions with circulating levels between 25 and 50% (Giri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%